End-Region Losses in High-Power Electrical Machines: Impact of Material Thickness on Eddy Current Losses in Clamping Structures - Walid Mohand Oussaid; Abdelmounaïm Tounzi; Raphaël Romary; Abdelkader Benabou; Walid Boughanmi; Daniel Laloy (Energies)
High-power electrical machines often utilize clamping structures composed of various materials with specific geometric dimensions to secure the stator laminations. These structures are exposed to end-region magnetic flux, which induces eddy currents, leading to significant power losses that reduce the machine’s efficiency. This study systematically investigates the impact of clamping plate thickness on eddy current losses across different materials and operating frequencies. A simplified experimental configuration was established to validate the numerical model developed using 3D Finite Element Method (FEM). This model was used to calculate the eddy current losses and analyze the influence of plate thickness under various conditions. A comprehensive parametric analysis was performed, revealing critical insights into the relationship between material properties, plate thickness, and loss generation. The findings indicate that while thinner plates exhibit higher current density, thicker plates provide a larger volume for current flow, resulting in varying loss patterns depending on the material’s electrical and magnetic properties. The study’s results offer valuable guidance for optimizing clamping structure designs in high-power electrical machines by selecting materials and thicknesses that minimize losses while maintaining mechanical integrity.